Contributions of Prominent Foreigners and Domestic Individuals to Mongolia's Development: A Historical Perspective - Miller, Antony D.; Gaanjuursuren, Jargalsaikhan (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the substantial contributions made by prominent foreigners to Mongolia through out history. Mongolia, located between China and Russia, has a rich cultural legacy and a distinct geopolitical position. Several prominent figures from other nations have played significant roles in supporting Mongolia in a variety of disciplines, including diplomacy, education, healthcare, and economic growth. This research intends to shed light on these contributions and their long-term influence on Mongolia's socioeconomic and scape. Mongolia has a long history of relations with outsiders, and numerous prominent figures from other nations have helped the country. This article features some noteworthy foreigners who have made contributions to Mongolian history.